Entre camisas negras e azuis: o futebol como um elemento de diplomacia cultural para o governo fascista de Mussolini - Viciguer, Enzo Toledo (2024)
Much more than a game played in four lines, football is also a political device used by many regimes for their self-promotion and legitimization of their governments. Undestanding the capabilities that football possesses, this paper proposes to analyze, within the concept of Cultural Diplomacy in International Relations, how calcio was used by the Italian fascist regime as a state policy to increase its international influence. Highlighting the changes proposed by Mussolini's government to the national structures of the game, as well as the regime's perception of the virtuous role of sport within Italian Society. This essay will focus on what Kruger (1999) considers to be the high point of the regime's enthusiasm, the conquests of the 1934 and 1938 World Cups, investigating how fascism appropriated sport and transformed it into the manifestation of the virtues of its regime through mechanisms of propagation and diffusion of its influence, regime and ideology on an international level arranged by Cultural Diplomacy between States